Contextual Guessing Technique in Reading - Syamsiah Depalina Siregar (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2019)
This research aimed to know whether students’ reading comprehension can improve with use Contextual Guessing Technique and to know how the implementation of this method in reading class. This research used action research classroom. The finding of the research was the students more enthusiast in answering the reading’s question. The test result came from first cycle and second cycle. It showed improvement. The conclusion was the students need learning technique relate with their learning level. Contextual Guessing Technique is one of the appropriate techniques in reading class for senior high students. This case proved by the students more motivated and spirit in learning English especially in reading. Therefore the students got good score.